Kajian Kapasitas Lentur Balok Beton Bertulangan Bambu Petung - Nuraeni, Reni; Widyarti, Meiske; Sapei, Asep (Jurnal Teknik Sipil dan Lingkungan, 2018)
Reinforced concrete generally use steel reinforce material. Steel is quarry material that someday be exhausted and relatively high price. Hence,need to find the substitution material which a more affordable with the structure power that equivalent. Bamboo can be assessed solution as a substitution material of steel reinforce. This research looked at a bending capacity of the bamboo petung  reinforce concrete beams with notch is 2 cm and 3 cm. The sectional form of the reinforce bamboo of arch ( 1 / 4 ) circle and  ( 1 / 2 ) circle.  Tensile testing sample of bamboo obtained average value of bamboo tensile strength  is 288.81 mpa .A mixture of concrete f‘c = 17.5 MPa with the mixtures by virtue of SNI 7394-2008 .The  testing results of compressive strength at the age of 3 days concrete 9.837 MPa . Sample  beams made about 9 type reinforcement .From the flexural testing at the age of 28 days type reinforcement TB4 have flexural strength of 10.167 MPa value flexural approach strength  steel reinforcement beams of 12.00024 Mpa.Keywords : bamboo petung, flexural beams, reinforcement bamboo